Politics of the 'Other' in India and China: Western concepts in non-western contexts - König, Lion; Chaudhuri, Bidisha (Routledge contemporary Asia series, 2016)
Foreword : Constructing and Deconstructing the "Other" in the Social Science Discourse / T.K. Oommen -- The Hindu Nationalist Strategy of Stigmatisation and Emulation of "Threatening Others" : An Indian Style Fascism? / Christophe Jaffrelot -- Stretching Secularism : Conceptual Equivocality in the Indian Context / Lion Koenig -- Muslim Citizens versus Citizen Muslims : A Study of Discursive Strategies in Contemporary India / Julten Abdelhalim -- "Back to the roots" : The Indigenisation of Western Party Politics in Post-colonial India / Clemens Spiess -- Indian Federalism : A Hybrid Solution to the Problem of Diversity and Political Order / Harihar Bhattacharyya -- Politics of "Good Governance" : "Otherising" Governance in India / Bidisha Chaudhuri -- Self and Other in the Making of Foreign Policy : The Terms of Discourse in Indo-European Relations / Subrata K. Mitra -- Class Politics and the Entrenchment of the Party-State in Modern China / Brian Tsui -- The Chinese Assimilation of "Social Class" : Intellectual Discourses on Jieji between 1899 and 1949 / Jeesoon Hong -- Chinese Dreams of Socialism : Visions of a Better Future / Gerda Wielander -- Democracy with Chinese Characteristics : The Primacy of the Nation / Robert Weatherley -- "Othering" in the Construction of Chinese Citizenship / Malgorzata Jakimóv and Elena Barabantseva -- "Renquan"-Chinese Human Rights : An "Import" from the West or a Chinese "Export"? / Yuka Kobayashi -- Soft Power in China : Adaptation and Development of a Fashionable Concept / Mareike Ohlberg -- Hegemony in Chinese? : Ba in Chinese International Relations / Astrid Nordin
Keywords: Aufsatzsammlung; Minderheitenpolitik; Nationalstaat; Staatsangehörigkeit; China; Nationalismus; Indien